UNDERSTANDING THE FACTORS INFLUENCING BANKING CUSTOMERS’ FINANCIAL ASSET OWNERSHIP - Aimatul Yumna; Joan Marta (Journal of Islamic Monetary Economics and Finance, 2021)
The objective of this study is to evaluate the factors which influence banking customers' financial asset ownership. Using the pyramid of Maslahah framework, the study classifies the needs of banking customers into four levels: those for basic financial services (hajjiyat); for financial assets for security or as a precaution (darruriyat); for financial assets for investment (tahsiniyah); and those for financial assets for religious purposes. To answer the research questions, a binomial logistic model was applied and the primary data were collected using a questionnaire survey with 300 respondents in Indonesia. It was found that the pattern of ownership of financial assets follows the order proposed in the theory of the pyramid of Maslahah. The study also found that financial asset ownership for transaction needs was mainly influenced by the variables of income and credit and that ownership of such assets for security or precautionary needs was largely determined by life cycle variables. In addition, ownership for investment needs was strongly influenced by the level of education, and for religious needs it was mainly determined by income levels and life cycle variables. The study findings provide important information for mapping the financial needs of Islamic banking customers.